2017
DOI: 10.1039/c7nj02580g
|View full text |Cite
|
Sign up to set email alerts
|

Energy storage applications of biomass-derived carbon materials: batteries and supercapacitors

Abstract: Recent advances in the application of biomass-derived carbon materials in batteries and supercapacitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(57 citation statements)
references
References 162 publications
0
57
0
Order By: Relevance
“…Energyf rom sunlight is stored as chemical energy in biomass and this energy can be widely used to meet our increasing energy needs, such as heating, cooking, and transport fuel. [54] In addition, BDC can also be derived from microorganisms, such as fungi (mushrooms and yeasts) and bacterial cellulose, [107,108] which can be considered as good regenerative biomass precursors due to their fast growth rate, richness in nature,and complexc hemical compositions. [106] The pyrolysis of variousb iomass precursors at high temperature under an inert gas leads to the formation of ap orous carbon skeleton.…”
Section: Carbon-based Materials Used As Electrode Materials For Ascsmentioning
confidence: 99%
“…Energyf rom sunlight is stored as chemical energy in biomass and this energy can be widely used to meet our increasing energy needs, such as heating, cooking, and transport fuel. [54] In addition, BDC can also be derived from microorganisms, such as fungi (mushrooms and yeasts) and bacterial cellulose, [107,108] which can be considered as good regenerative biomass precursors due to their fast growth rate, richness in nature,and complexc hemical compositions. [106] The pyrolysis of variousb iomass precursors at high temperature under an inert gas leads to the formation of ap orous carbon skeleton.…”
Section: Carbon-based Materials Used As Electrode Materials For Ascsmentioning
confidence: 99%
“…The SSA of a-PANF is up to 2157.4 m 2 g À1 ,w hich is considerably highert han the 1832 m 2 g À1 of p-PANF.T he corresponding pore size distribution was estimated from the adsorption branches of the isotherms. [16] Furthermore, the as-electrospun fibers are interconnectedw ith one another,p roducing ah yperbranched network structure with numerous macropores (> 50 nm), and the latter serve as ion-buffering reservoirs to minimize the diffusion distanceso felectrolyte ions to the interior surfaces. The total pore volumeo fa -PANF is 1.03 cm 3 g À1 and the fraction of micropores is 73.4 %, which indicates that the porous structureo fa -PANF is dominated by micropores.I th as been reported that micropores of sizes between 0.8 and 1.4 nm are fully accessible to PF 6 À anions of electrolytes.…”
Section: Morphological and Physical Characterizationmentioning
confidence: 99%
“…Electrospinning is as imple and scalablet echnique for the preparation of continuousf ibers with diameters rangingf rom nanometers to micrometers by applying an electrostatic force between apolymer solutiona nd am etallic collector. [16] In this work, we reportt he preparation of hierarchical porousc arbon fibers with improvedd egree of graphitization for LIC applications. However,c onventionalp olymer-derived amorphous carbon usually exhibitsarelativelyl ow degree of graphitizationdue to the presence of large amounts of defects, which leads to limited electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilization of biomass waste in the production of electrode materials is as mart way of cutting the costs of the raw materials withoutc ompromising the positive environmental impact.T od ate, al arge number of biomass-derived carbon materials have been extensively reported in both symmetric and asymmetricc onfigurations, with improved electrochemical properties [31] compared to commercially available AC. [32][33][34][35][36][37][38] However,d isappointingly,t here has been very limited work on their use in LIC assemblies. As such, this Minireview describes the performanceo fs uch biomass-derivedc arbonaceous materials in LIC configurations.…”
Section: Introductionmentioning
confidence: 99%